Upaya Peningkatan Partisipasi Masyarakat dalam Pemanfaatan Aplikasi Layanan Aspirasi dan Pengaduan Online Rakyat di Kota Cimahi - Rodlial Ramdhan Tackbir Abubakar; Ghea Ananda Nurhaliza (Jurusan Administrasi Publik FISIP UIN SGD Bandung, 2023)
The purpose of this study is to find out, identify the inhibiting factors, and design recommendation efforts for the implementation of LAPOR! in Cimahi City for increased community participation in the supervision of public programs and services in Cimahi City. The research method used is a descriptive qualitative method. Data collection was carried out by interviews, observations, and documentation studies. Data analysis is carried out by collecting data, reducing data, presenting data, and drawing conclusions. Then this data is tested for validity with Source Triangulation. Based on the results of the study the implementation of LAPOR! in Cimahi City has not run optimally. This is due to several hindering factors such as the lack of human resources managers, the commitment of regional devices to implement LAPOR! is still low, lack of supporting policies, budget constraints, and there is no information media about LAPOR! for the community. There are several efforts recommended in this study including the creation of infographics as an information medium, integrating services, enforcing official policies of the city government, improving the skills and capacity of human resources through training and coaching in the field of ICT, consistency, and expansion of socialization reach, as well as conducting regular monitoring and evaluation of realization.